Legal Protection for Unilateral Layoffs of Additional Workers at Teluk Nibung Port Following the Enactment of Government Regulation No. 35 of 2021 from a Maqashid Sharia Perspective - Silvia Arma; Muhammad Ramadhan (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Additional Workers (TKT) at Teluk Nibung Port in Tanjung Balai City are vulnerable subjects in industrial relations in Indonesia. This study aims to analyze the legal protection for TKT who experienced unilateral termination of employment (PHK) by the port in 2023, after working since 1996, without compensation. Legally, the status of workers who worked for years with verbal agreements and the continuous nature of the work indicates an indefinite-term employment relationship (PKWTT), regardless of the formal designation "Additional." Although the Government has issued Government Regulation Number 35 of 2021 as a derivative of the Omnibus Law of the Job Creation Law, the regulation still causes ambiguity, especially regarding the status of workers who are not formally registered and the mechanism for unilateral layoffs that violate procedures. From the perspective of Maqashid sharia, protection for TKT is crucial in order to achieve the benefit (welfare) which is the main objective of sharia, especially in maintaining the soul (hifzh an-nafs) through fulfilling the right to livelihood (hifzh al-mal). Layoffs without proper compensation have the potential to threaten the maqashid and are a form of injustice that must be resolved through industrial relations legal channels.